Conditioning regimens for allogeneic hematopoietic cell transplantation in acute myeloid leukemia: Real-world data from the Japanese registry studies - Yanada, Masamitsu; Harada, Kaito; Shimomura, Yoshimitsu; Arai, Yasuyuki; Konuma, Takaaki (Frontiers in Oncology, 2022)
Conditioning regimens play a crucial role in preventing relapse of acute myeloid leukemia (AML) following allogeneic hematopoietic cell transplantation (HCT). In early times, myeloablative conditioning was used exclusively, but it was associated with significant toxicity. However, the advent of reduced-intensity conditioning has allowed allogeneic HCT to be performed more safely, leading to an expansion of our choices for conditioning regimens. As the transplantation methods have become highly diversified, it is reasonable to determine an optimal conditioning regimen in consideration of patient-, disease-, and transplantation-related factors. In this context, large-scale registry-based studies provide real-world data to allow for a detailed evaluation of the utility of individual conditioning regimens in specific clinical settings. The Japanese Society for Transplantation and Cellular Therapy has been conducting a nationwide survey for HCT since 1993 that currently covers >99% of all the transplantation centers nationwide, and >1,000 allogeneic HCTs performed for adults with AML are registered per year. We have been using the registry data to implement a number of studies focusing on adults with AML, and the large number of patients registered consecutively from nearly all transplantation centers nationwide represent real-world practice in Japan. This article reviews and discusses the results obtained from our registry-based studies pertaining to various conditioning regimens.